Perempuan Memberontak: Perlawanan Perempuan Minangkabau terhadap Kolonialisme Belanda di Sumatera Barat 1908-1942 - Dedi Arsa (Kafa`ah: Journal of Gender Studies, 2017)
The women play important position against the Dutch colonialism in West Sumatra. The image of women as a representation of tenderness and squeezes were in different with the condition that they can also be radical. This study examined the involvement of Minangkabau women in their struggle towards the colonialism and the consequences they faced against their resistance. It was found that women have special position in the Indonesian struggle opposing the Dutch colonialism in West Sumatra. The image of women who were closely refers to tenderness and squeezing are much differ from it was in colonial era, that they were hard-hearted and radicalism. By using Historical approach this study found that in the nineteenth century there was almost no resistance to colonization involved the women. It did not happen until the twentieth century where women were involved, in the form of a physical (violent) resistance and with a radical-political path. The average resistance figures were imprisoned or thrown away, but each character carried a different fate, half the loneliness in wasted anguish and the other half get the joys from the public.